2012
DOI: 10.4103/0971-4065.103906
|View full text |Cite
|
Sign up to set email alerts
|

The Kt/V by ionic dialysance: Interpretation limits

Abstract: The availability of hemodialysis machines equipped with online clearance monitoring (OCM) allows frequent assessment of dialysis efficiency and adequacy without the need for blood samples. Accurate estimation of the urea distribution volume (V) is required for Kt/V calculated from OCM to be consistent with conventional blood sample-based methods. A total of 35 patients were studied. Ionic dialysance was measured by conductivity monitoring. The second-generation Daugirdas formula was used to calculate the Kt/V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 21 publications
0
8
0
16
Order By: Relevance
“…It is done by measuring ionic dialysance through conductivity measurements of dialysate using online clearance monitor. [ 46 ]…”
Section: Discussionmentioning
confidence: 99%
“…It is done by measuring ionic dialysance through conductivity measurements of dialysate using online clearance monitor. [ 46 ]…”
Section: Discussionmentioning
confidence: 99%
“…This method does not require blood sampling and can be used with each dialysis treatment. However, more recent studies has shown that Kt/V OCM with V determined by Watson formula, leads to systematic underestimation of Kt/V by 22%–24% when comparing to Kt/V derived from urea reduction using the Daugirdas second generation equation …”
Section: Clinical Standard and Targetsmentioning
confidence: 96%
“…In practice, the ionic dialyzer clearance (Kd‐cond) obtained in this fashion has been used to estimate Kt/V, by multiplying Kd‐cond by the dialysis session length (t), and dividing by an estimate of the urea distribution volume (V), the latter usually estimated from either anthropometry (eg, the Watson volume), or from bioimpedance, given that the urea distribution volume is closely related to the total body water . However, this conductivity based Kt/V correlates only modestly with Kt/V derived from predialysis and postdialysis SUN measurement . For this reason, the use of conductivity clearance monitoring has not replaced monthly urea modeling, with its attendant complexities (staff time, safety issues, and laboratory expenses) associated with obtaining the postdialysis urea nitrogen blood sample.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, this conductivity based Kt/V correlates only modestly with Kt/V derived from predialysis and postdialysis SUN measurement. [7][8][9] For this reason, the use of conductivity clearance monitoring has not replaced monthly urea modeling, with its attendant complexities (staff time, safety issues, and laboratory expenses) associated with obtaining the postdialysis urea nitrogen blood sample.…”
mentioning
confidence: 99%